Large Extracellular Vesicles: Have We Found the Holy Grail of Inflammation? - Słomka, Artur; Urban, Sabine Katharina; Lukacs-Kornek, Veronika; Żekanowska, Ewa; Kornek, Miroslaw (Frontiers in Immunology, 2018)
The terms microparticles (MPs) and microvesicles (MVs) refer to large extracellular vesicles (EVs) generated from a broad spectrum of cells upon its activation or death by apoptosis. The unique surface antigens of MPs/MVs allow for the identification of their cellular origin as well as its functional characterization. Two basic aspects of MP/MV functions in physiology and pathological conditions are widely considered. Firstly, it has become evident that large EVs have strong procoagulant properties. Secondly, experimental and clinical studies have shown that MPs/MVs play a crucial role in the pathophysiology of inflammation-associated disorders. A cardinal feature of these disorders is an enhanced generation of platelets-, endothelial-, and leukocyte-derived EVs. Nevertheless, anti-inflammatory effects of miscellaneous EV types have also been described, which provided important new insights into the large EV-inflammation axis. Advances in understanding the biology of MPs/MVs have led to the preparation of this review article aimed at discussing the association between large EVs and inflammation, depending on their cellular origin.